STIM1‐mediated calcium influx controls antifungal immunity and the metabolic function of non‐pathogenic Th17 cells - Sascha Kahlfuss; Ulrike Kaufmann; Axel R Concepcion; Lucile Noyer; Dimitrius Raphael; Martin Vaeth; Jun Yang; Priya Pancholi; Mate Maus; James Muller; Lina Kozhaya; Alireza Khodadadi‐Jamayran; et al. (EMBO Molecular Medicine)
Abstract Immunity to fungal infections is mediated by cells of the innate and adaptive immune system including Th17 cells. Ca2+ influx in immune cells is regulated by stromal interaction molecule 1 (STIM1) and its activation of the Ca2+ channel ORAI1. We here identify patients with a novel mutation in STIM1 (p.L374P) that abolished Ca2+ influx and resulted in increased susceptibility to fungal and other infections. In mice, deletion of STIM1 in all immune cells enhanced susceptibility to mucosal C. albicans infection, whereas T cell‐specific deletion of STIM1 impaired immunity to systemic C. albicans infection. STIM1 deletion impaired the production of Th17 cytokines essential for antifungal immunity and compromised the expression of genes in several metabolic pathways including Foxo and HIF1α signaling that regulate glycolysis and oxidative phosphorylation (OXPHOS). Our study further revealed distinct roles of STIM1 in regulating transcription and metabolic programs in non‐pathogenic Th17 cells compared to pathogenic, proinflammatory Th17 cells, a finding that may potentially be exploited for the treatment of Th17 cell‐mediated inflammatory diseases.